Continuous Local Intra-Arterial Nimodipine for the Treatment of Cerebral Vasospasm - Logallo, Nicola; Bøthun, Marianne Lundervik; Guttormsen, Anne Berit; Holmaas, Gunhild; Kråkenes, Jostein; Thomassen, Lars; Svendsen, Frode; Helland, Christian A. (Journal of Neurological Surgery Reports, 2015)
Vasospasm (VSP) is one of the major causes for prolonged neurologic deficit in patients with aneurysmal subarachnoid hemorrhage. Few case series have reported about continuous local intra-arterial nimodipine administration (CLINA) in refractory VSP. We report our experience with CLINA in a patient with refractory cerebral VSP.
Keywords: aneurysmal subarachnoid hemorrhage; intra-arterial nimodipine; transcranial color-coded sonography; vasospasm